Estimating Herd Immunity to Amphibian Chytridiomycosis in Madagascar Based on the Defensive Function of Amphibian Skin Bacteria - Bletz, Molly C.; Myers, Jillian; Woodhams, Douglas C.; Rabemananjara, Falitiana C. E.; Rakotonirina, Angela; Weldon, Che; Edmonds, Devin; Vences, Miguel; Harris, Reid N. (Frontiers in Microbiology, 2017)
For decades, Amphibians have been globally threatened by the still expanding infectious disease, chytridiomycosis. Madagascar is an amphibian biodiversity hotspot where Batrachochytrium dendrobatidis (Bd) has only recently been detected. While no Bd-associated population declines have been reported, the risk of declines is high when invasive virulent lineages become involved. Cutaneous bacteria contribute to host innate immunity by providing defense against pathogens for numerous animals, including amphibians. Little is known, however, about the cutaneous bacterial residents of Malagasy amphibians and the functional capacity they have against Bd. We cultured 3179 skin bacterial isolates from over 90 frog species across Madagascar, identified them via Sanger sequencing of approximately 700 bp of the 16S rRNA gene, and characterized their functional capacity against Bd. A subset of isolates was also tested against multiple Bd genotypes. In addition, we applied the concept of herd immunity to estimate Bd-associated risk for amphibian communities across Madagascar based on bacterial antifungal activity. We found that multiple bacterial isolates (39% of all isolates) cultured from the skin of Malagasy frogs were able to inhibit Bd. Mean inhibition was weakly correlated with bacterial phylogeny, and certain taxonomic groups appear to have a high proportion of inhibitory isolates, such as the Enterobacteriaceae, Pseudomonadaceae, and Xanthamonadaceae (84, 80, and 75% respectively). Functional capacity of bacteria against Bd varied among Bd genotypes; however, there were some bacteria that showed broad spectrum inhibition against all tested Bd genotypes, suggesting that these bacteria would be good candidates for probiotic therapies. We estimated Bd-associated risk for sampled amphibian communities based on the concept of herd immunity. Multiple amphibian communities, including those in the amphibian diversity hotspots, Andasibe and Ranomafana, were estimated to be below the 80% herd immunity threshold, suggesting they may be at higher risk to chytridiomycosis if a lethal Bd genotype emerges in Madagascar. While this predictive approach rests on multiple assumptions, and incorporates only one component of hosts' defense against Bd, their culturable cutaneous bacterial defense, it can serve as a foundation for continued research on Bd-associated risk for the endemic frogs of Madagascar.